Frontispiece: Thermally Tunable Hydrogels Displaying Angle‐Independent Structural Colors. Issue 51 (7th December 2015) - Ohtsuka, Yumiko; Seki, Takahiro; Takeoka, Yukikazu
Abstract : Angle‐Independent Structural Color In their Communication on page 15368 ff., Y. Takeoka et al. report on thermally tunable hydrogels displaying angle‐independent structural colors that were prepared from colloidal amorphous array templates and carbon black.